Prediksi Penilaian Kinerja Guru Dengan Menggunakan Metode Fuzzy Logic Di Sekolah MIS Ibnu Abbas Sepatan Timur - Fikri Awaludin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Teacher performance is an attitude carried out by educators or teachers in the process of teaching and learning activities (KBM), one of which is how a teacher or educator plans learning, implements classroom learning, and assesses the learning outcomes of these students. Therefore, school management must evaluate teaching and learning activities in the school environment, in accordance with the competencies that must be possessed by teachers or educators. In this study, we will apply the Fuzzy Logic System to the prediction of teacher performance assessments at MIS Ibnu Abbas, East Sepatan, so that the teacher performance appraisal process becomes faster, more effective, and minimizes human error in the implementation of this teacher performance assessment. So that the teacher performance appraisal system can help the principal (headmaster) in supervising and making decisions or more accurate assessments.